The Association Between Stress Levels and Nutritional Status Among Preclinical Medical Students at The State University of Gorontalo - Nurqurratul Aini S. Djunubi; Cecy Rahma Karim; Sri Manovita Pateda; Vivien Novarina A. Kasim; Sri Andriani Ibrahim (Biomedical Journal of Indonesia, 2026)
Introduction. Malnutrition remains a global public health concern with significant implications for young adults, including medical students who are exposed to high academic demands that may induce persistent stress and subsequently affect eating behavior and nutritional status. This study aimed to identify stress levels and nutritional status and to analyze the relationship between the two among preclinical medical students at the Faculty of Medicine, Gorontalo State University. Methods. An observational analytical study with a cross-sectional design was conducted involving 191 respondents selected through total sampling. Stress levels were assessed using the Medical Student Stressor Questionnaire (MSSQ), while nutritional status was determined based on Body Mass Index (BMI) obtained from standard anthropometric measurements. Data were analyzed using Spearman’s correlation test. Results. The results showed that most students experienced moderate stress levels (51.8%), with academic-related stressors being the most dominant, and the majority of respondents had normal nutritional status (56.5%). Bivariate analysis demonstrated no significant correlation between stress levels and nutritional status (r = −0.131; p = 0.071). Conclusion. In conclusion, stress levels were not significantly associated with nutritional status among preclinical medical students. Other factors, such as daily calorie intake, physical activity, sleep duration, and genetic or family history, may play a more prominent role in determining nutritional status. Nevertheless, stress management interventions and the promotion of healthy lifestyles remain important to support the overall well-being of medical students.